The Myths and Realities of Teaching Vocational Subjects in Tertiary Institutions in Nigeria - Otuaga, O. Uviomo-Mayes; Efajemue, O. O.; Otuaga, Efemena E. (Mediterranean Journal of Social Sciences, 2011)
Myths are narratives formative or reflective of social order or values within a culture. These narratives are believed tobe true from within the associated faith system within any given culture there may be sacred and secular myths coexisting. Thefocus of this paper is the myths and realities of teaching vocational subjects in tertiary institutions in Nigeria. The paper gives theconcept of myths and realities (learning technology: the myths and facts). It also discusses the E-learning as obtained in modernworld. The paper also proffers invaluable suggestions on how the youths can be empowered for sustainable development.